Chlorophyll Fluorescence parameters, SPAD chlorophyll and yield in Brassica cultivars - Pushp Sharma (Journal of Oilseed Brassica, 2026)
In order to evaluate chlorophyll fluorescence fluctuations in different cultivars of Brassica, a factorialexperiment with randomized complete block design was laid during two winter seasons 2011-12 and 2012-13.Cultivars differed significantly for SPAD chlorophyll values, different components of chlorophyll fluorescenceand seed yield. Environment had a profound effect on all the parameters studied except Fv/Fm and Fv/Fo.However, positive relation existed between SY and Fv/Fm (0.268), Fv/Fo (0.389), ETR (0.0118) and SPAD(0.636**). RLC1 (B.juncea ) and Hyola PAC401(B.napus, hybrid) out yielded the other cultivars indicatingcultivars with less disruption in photochemical efficiency of PSII, higher electron transport rate and SPADchlorophyll greenness were higher yielders.